Successful Treatment of Giant Basal Cell Carcinoma with Topical Imiquimod 5% Cream with Long Term Follow-up - Chun-Guang, M (Indian J Dermatol, 2014)
The use of the topical Imiquimod 5% cream offers a noninvasive, nonsurgical, and an effective option for the treatment of primary small (<2 cm) superficial basal cell carcinoma (sBCC). However, reports about successful treatment of giant (>5 cm) BCC with topical Imiquimod 5% cream are rare. We present our experience in the treatment of two giant tumors (6 × 8 cm(2), 5.2 × 4.2 cm(2)) of BCC on the face with Imiquimod 5% cream, 2 to 3 days/week for 12 weeks. Both the tumors were cured with clinical and pathological evidence, one with 6-year follow-up and the other with 3.5-year follow-up.